Agriculture and intellectual property rights: economic, institutional and implementation issues in biotechnology. - Carlson, G. A.; Evenson, R. E.; Santaniello, V.; Zilberman, D. (Wallingford :CABI Publishing, 2000)
This book has arisen from the conference entitled 'The shape of the coming agricultural biotechnology transformation: strategic investment and policy approaches from an economic perspective' convened by the international Consortium on Agricultural Biotechnology Research (ICABR), held in Rome, June 17-19, 1999. Papers are divided between four sections covering: legal systems (5 papers); economic issues (5 papers); biotechnology inventions (2 papers); and case studies (2 papers)- North America and Canada.
Keywords: DD500 - Laws and Regulations; FF020 - Plant Breeding and Genetics; WW000 - Biotechnology (General), (Revised June 2002); Canada; North America